Effects of Kinesio Tape to Reduce Hand Edema in Acute Stroke. Issue 3 (May 2013) - Bell, Alison; Muller, Melissa
Abstract : Objective : The purpose of the study was to evaluate the efficacy of Kinesio Tape (Kinesio USA, Albequerque, NM) for reducing hand edema in individuals with hemiplegia post stroke.Methods : Seventeen individuals who experienced acute stroke were screened for visual signs of edema and were randomly assigned to experimental and control groups. The experimental group received Kinesio Tape that was applied to hand and forearm for 6 days in combination with standard therapy; the control group received standard therapy. Blinded raters assessed edema reduction via circumferential measurements.Results : Application of Kinesio Tape did not result in statistically significant reduction in edema. Large and medium effect sizes were seen for edema reduction at the metacarpophalangeal and wrist joints, respectively, with Kinesio Tape.Conclusion : Further research is warranted to investigate the utility of Kinesio Tape in edema reduction.